Authority, Space, and Literary Media—Eucherius' Epistula de laude eremi and Authority Changes in Late Antique Gaul. Issue 3 (16th November 2017) - Feldt, Laura
Abstract : This article discusses religious authority changes in late antique Gaul, where spatial and literary media played important roles in how religious authority was maintained, negotiated, and transformed in Western Europe in the aftermath of the Roman empire. The analysis uses theories of social space to analyse and discuss how the authority of the desert space, and ascetic practice, was negotiated through the literary medium of Eucherius of Lyon's Epistula de laude eremi (In Praise of the Desert), as well as how the authority of the text as a medium is constructed. This analysis then forms the basis for a discussion of religious authority changes in late Antique Gaul following the success of ascetics as bishops, and the role of spatial and literary media in this process. In a world of large scale societal changes, literary media promoting ascetic holy figures, and the ascetic space of the desert, played a decisive role in transformations of authority and in negotations of the meanings of authoritative texts. Such media were created and used by ascetics, bishops, and theologians as means with which to change forms of religious authority, in an era in which the status of asceticism was a matter of contention and the authority of monks and church leaders was insecure. The authority transformations of the era became consequential for Western European history.